The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1177/001440298705400105
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Regular and Special Educators to Teach Students with Handicaps

Abstract: A mailed questionnaire containing 99 demographic and attitudinal variables regarding handicap integration drew responses from 128 regular educators and 133 special educators in 21 school districts. Separate discriminant function analyses using “I would be willing to teach a student with (a handicap)” as the criterion variable were conducted for the two groups of educators. A comparison of the group profiles revealed few similarities. Regular educator willingness depended more heavily upon demographic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 6 publications
1
14
0
2
Order By: Relevance
“…One student said:`This questionnaire has made me realise just how very little I know about children with language and speech di culties and I would like to learn more about such children's needs.' This is supported by previous research ®ndings over the last 25 years (Baker and Gottlieb 1980, Gans 1985, Semmel et al 1991, Whinnery et al 1991, Houck and Rogers 1994. Gallagher (1985), Gans (1985) and Leyser (1988) thought that training could increase awareness and that`students' attitudes become more positive after extended training' (Gallagher 1985: 694).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…One student said:`This questionnaire has made me realise just how very little I know about children with language and speech di culties and I would like to learn more about such children's needs.' This is supported by previous research ®ndings over the last 25 years (Baker and Gottlieb 1980, Gans 1985, Semmel et al 1991, Whinnery et al 1991, Houck and Rogers 1994. Gallagher (1985), Gans (1985) and Leyser (1988) thought that training could increase awareness and that`students' attitudes become more positive after extended training' (Gallagher 1985: 694).…”
Section: Discussionsupporting
confidence: 77%
“…Lack of training has already been discussed. Lack of resources, which included both materials and personnel, were also mentioned by Gans (1985), Coates (1989) and Myles and Simpson (1992). Lack of time was also a factor in studies by Semmel et al (1991), Diebold and von Eschenbach (1991) and Gans (1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evaluative research on these programs offers relatively discouraging results. Gans (1987) sees these as insufficient responses to teachers' difficulties, as such difficulties are rooted in beliefs, which are engulfed by emotions. In other words, we must correctly understand the sources of tension before we can effectively address the issue.…”
Section: Challenging Teacher Beliefs Via Counseling Methods: a Descrimentioning
confidence: 99%
“…General education teachers' willingness to assume instructional responsibility for special education students is a critical component for implementation (Kauffman, Gerber, & Semmel, 1988;McKinney 8c Hocutt, 1988), and frequently general education teachers are cited as reluctant to assume this responsibility (Gans, 1985(Gans, , 1987Hoover 8c Cessna, 1984;Knoff, 1985;Moore 8c Fine, 1978;Pedhazur-Schmelkin, 1981;Stephens 8c Braun, 1980). Rodden-Nord, Shinn, and Good (1992) demonstrated that general education teachers' willingness to reintegrate special education students into their classrooms for reading instruction was influenced by the kind of testing data they received.…”
Section: Potential Benefits Of This Reintegration Approachmentioning
confidence: 99%